Mindestlohnregelungen im Maler- und Lackiererhandwerk: Eine Wirkungsanalyse - Bernhard Boockmann; Michael Neumann; Pia Rattenhuber (Journal for Labour Market Research, 2012)
– The introduction of the minimum wage in the German painter and varnisher trade in 2003 is used as a natural experiment to study the effects of minimum wages on wages and employment. We find a significant positive effect on the average hourly wage of skilled workers in East Germany, but not in West Germany and not for unskilled workers. This finding corresponds to the differences in the strength of the minimum wage across these groups. No significant positive or negative employment effects are found. Recent survey results indicate the continuing relevance of the minimum wage in East Germany.
Keywords: J38; J31; 330; Mindestlohn - Erfolgskontrolle; Malerhandwerk; Lackierer; Maler; Handwerksberufe; Einkommenseffekte; Beschäftigungseffekte; regionaler Vergleich; Facharbeiter; Ungelernte; Lohnhöhe; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland